First observation of the decay B0→D0D[bar]0K+π− - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Dziewiecki, Michal; Frau, Giulia; Gerick, David; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Physical review, 2020)
The first observation of the decay B0→D0¯D0K+π− is reported using proton-proton collision data corresponding to an integrated luminosity of 4.7 fb−1 collected by the LHCb experiment in 2011, 2012 and 2016. The measurement is performed in the full kinematically allowed range of the decay outside of the D*− region. The ratio of the branching fraction relative to that of the control channel B0→D*−D0K+ is measured to be R=(14.2±1.1±1.0)%, where the first uncertainty is statistical and the second is systematic. The absolute branching fraction of B0→D0¯D0K+π− decays is thus determined to be B(B0→D0¯D0K+π−)=(3.50±0.27±0.26±0.30)×10−4, where the third uncertainty is due to the branching fraction of the control channel. This decay mode is expected to provide insights to spectroscopy and the charm-loop contributions in rare semileptonic decays.